United Kingdom : Financial Sector Assessment Program Technical Notes and Detailed Standards Assessments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This technical note reviews the Financial Sector Assessment Program of the United Kingdom. It examines the United Kingdom's public debt management practices using the IMF-World Bank Guidelines for Public Debt Management as a framework. It analyzes the government's Code for Fiscal Stability, transparency, accountability, debt strategy, and risk management framework. It also provides a detailed assessment of the antimoney laundering and combating the financing of terrorism regime and compliance of the Basel Core Principles of the United Kingdom.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet